(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Vegetable oils are triglyceride extracts derived from plant sources, consisting of fatty acid chains that can be saturated or unsaturated hydrocarbons. These oils are classified as simple triglycerides or mixed triglycerides based on their composition. The level of saturation or unsaturation is quantified by the iodine value of the oil sample. This research aimed to compare the iodine values of four different vegetable oils: Mustard oil, Safflower oil, Sunflower oil, and Coconut oil (both marketed and crude samples). The samples were procured from general provision stores and raw material production plants. The vegetable oils were analysed for their iodine values, yielding the following results: Sunflower oil (marketed) = 104.05 and (crude) = 158.62, Coconut oil (marketed) = 209.38 and (crude) = 38.07, Mustard oil (marketed) = 285.52 and (crude) = 171.31, Safflower oil (marketed) = 228.42 and (crude) = 133.24, etc. These values were evaluated and calculated in the institute laboratory.